Investigation of Emissions Characteristics of Secondary Butyl Alcohol-Gasoline Blends in a Port Fuel Spark Ignition Engines - I. M., Yusri; R., Mamat; Amir, Aziz; Ahmad Fitri, Yusop; Awad, Omar I.; S. M., Rosdi (2016)
Exhaust emissions especially from light duty gasoline engine are a major contributor to air pollution due to the large number of vehicles on the road. The purpose of this study is to experimentally analyse the exhaust pollutant emissions of a four-stroke port fuel spark ignition engines operating using secondary butyl alcohol–gasoline blends by percentage volume of 5% (GBu5), 10% (GBu10) and 15% (GBu15) of secondary butyl- alcohol (2-butanol) additives in gasoline fuels at 50% of wide throttle open. The exhaust emissions characteristics of the engine using blended fuels was compared to the exhaust emissions of the engine with gasoline fuels (G100) as a reference fuels. Exhaust emissions analysis results show that all of the blended fuels produced lower CO by 8.6%, 11.6% and 24.8% for GBu5, GBu10 and GBu15 respectively from 2500 to 4000 RPM, while for HC, both GBu10 and GBu15 were lower than that G100 fuels at all engine speeds.